2019
DOI: 10.2144/fsoa-2018-0123
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Recall Pneumonitis in the Setting of Immunotherapy and Radiation: a Focused Review

Abstract: Radiation recall pneumonitis (RRP) is an entity described as pneumonitis localized to a previously irradiated field after exposure to a systemic agent. It has previously been described in the literature in the context of chemotherapeutic agents as well as certain biologics. With immunotherapy taking a more prominent role in the treatment of several different malignancies and its own baseline risk of pneumonitis, it is important to explore the likelihood of RRP, specifically in those patients who have been prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 27 publications
1
58
0
1
Order By: Relevance
“…Two patients treated with nivolumab were reported to suffer from RRP within two years of radiotherapy completion, which is different from the windows for chemotherapy and targeted therapy 109 . RRP triggered by pembrolizumab has also been detailed in one case report 110 . Oncologists should be alert for RRP when radiological findings occur in irradiated areas following the application of drugs.…”
Section: Radiation Recall Pneumonitis After Immunotherapy Should Be Cmentioning
confidence: 98%
“…Two patients treated with nivolumab were reported to suffer from RRP within two years of radiotherapy completion, which is different from the windows for chemotherapy and targeted therapy 109 . RRP triggered by pembrolizumab has also been detailed in one case report 110 . Oncologists should be alert for RRP when radiological findings occur in irradiated areas following the application of drugs.…”
Section: Radiation Recall Pneumonitis After Immunotherapy Should Be Cmentioning
confidence: 98%
“…Programmed cell death 1 (PD-1)/ Programmed cell death 1 ligand 1 (PD-L1) inhibition alone can cause immune-mediated pneumonitis in less than 5% [145]. Furthermore, radiation recalls several months after thoracic radiotherapy while ICI is still being administered have been described in some cases [144,146]. The first systematic retro-and prospective studies have shown acceptable toxicity of sequential and concurrent radio-immunotherapy [147][148][149][150].…”
Section: Treatment-related Risk Factors Of Ripmentioning
confidence: 99%
“…everolimus, sunitinib, erlotinib) (9-11). However, the literature is much sparser on RRP arising in the context of immunotherapy (12)(13)(14), with the largest case series containing only two patients (13). Here, we describe three cases of suspected immunotherapy-induced RRP treated at our institution.…”
Section: Introductionmentioning
confidence: 99%